Patterns of Genome-Wide Variation, Population Differentiation and SNP Discovery of the Red Banded Stink Bug (Piezodorus guildinii) - Zucchi, Maria I. (Sci Rep, 2019)
Unravelling the details of range expansion and ecological dominance shifts of insect pests has been challenging due to the lack of basic knowledge about population structure, gene flow, and most importantly, how natural selection is affecting the adaptive process. Piezodous guildinii is an emerging pest of soybean in the southern region of the United States, and increasingly important in Brazil in recent years. However, the reasons P. guildinii is gradually becoming more of a problem are questions still mostly unanswered. Here, we have genotyped P. guildinii samples and discovered 1,337 loci containing 4,083 variant sites SNPs that were used to estimate genetic structure and to identify gene candidates under natural selection. Our results revealed the existence of a significant genetic structure separating populations according to their broad geographic origin, i.e., U.S. and Brazil, supported by AMOVA (F(GT) = 0.26), STRUCTURE, PCA, and F(ST) analyses. High levels of gene flow or coancestry within groups (i.e., within countries) can be inferred from the data, and no spatial pattern was apparent at the finer scale in Brazil. Samples from different seasons show more heterogeneous compositions suggesting mixed ancestry and a more complex dynamic. Lastly, we were able to detect and successfully annotated 123 GBS loci (10.5%) under positive selection. The gene ontology (GO) analysis implicated candidate genes under selection with genome reorganization, neuropeptides, and energy mobilization. We discuss how these findings could be related to recent outbreaks and suggest how new efforts directed to better understand P. guildinii population dynamics.